2019
DOI: 10.1136/gutjnl-2019-318672
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional cytometric analysis of colorectal cancer reveals novel mediators of antitumour immunity

Abstract: ObjectiveA comprehensive understanding of anticancer immune responses is paramount for the optimal application and development of cancer immunotherapies. We unravelled local and systemic immune profiles in patients with colorectal cancer (CRC) by high-dimensional analysis to provide an unbiased characterisation of the immune contexture of CRC.DesignThirty-six immune cell markers were simultaneously assessed at the single-cell level by mass cytometry in 35 CRC tissues, 26 tumour-associated lymph nodes, 17 color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 59 publications
(57 reference statements)
10
93
1
Order By: Relevance
“…State-of-the-art technologies like single-cell RNA-sequencing (173) and high-dimensional mass spectrometry (CyTOF) analysis (179) have allowed us to investigate ILCPs, delineate distinct ILCs subsets and their developmental pathways, and identify novel mediators of antitumor immunity at single-cell resolution levels. These studies present new perspectives for exploring the complexity of ILCs in the diverse context of cancers and allow effective manipulation of ILC immunosurveillance to achieve optimal therapeutic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…State-of-the-art technologies like single-cell RNA-sequencing (173) and high-dimensional mass spectrometry (CyTOF) analysis (179) have allowed us to investigate ILCPs, delineate distinct ILCs subsets and their developmental pathways, and identify novel mediators of antitumor immunity at single-cell resolution levels. These studies present new perspectives for exploring the complexity of ILCs in the diverse context of cancers and allow effective manipulation of ILC immunosurveillance to achieve optimal therapeutic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…These intraepithelial ILC1s can be activated by chemokines and cytokines such as IL-18 produced by intestinal epithelial cells (63) or IL-12 from dendritic cells and monocytes (62). This induces IFN-γ production in ILC1 which, in contrast to previously mentioned studies (59,60), drives the pathogenesis of anti-CD40-induced colitis in Rag1 −/− mice (62) ( Table 3 and Figure 1A). Given these divergent outcomes, further studies are required to analyze the exact role of intraepithelial ILC1, their receptor expression and cytokine production using genetically-modified conditionallydeficient mice and human samples.…”
Section: Type 1 Innate Lymphoid Cellsmentioning
confidence: 91%
“…High-dimensional cytometric analyses have revealed that human colorectal tumors are highly infiltrated by NK cells and intraepithelial-like ILC1 (59,60). They secrete cytotoxic molecules such as granzymes and perforin (59,60) and cytokines such as IFN-γ following stimulation (59), making them key potential players in cytotoxic anti-tumor responses ( Figure 1A).…”
Section: Type 1 Innate Lymphoid Cellsmentioning
confidence: 99%
See 2 more Smart Citations